Behavioral finance dalam pengambilan keputusan keuangan pada umkm di Provinsi Bali - Laksmana, Komang Agus Rudi Indra (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
This study examines the role of behavioral finance of MSMEs in Bali province in making financial decisions, both financing decisions, investment and profit distribution policies. This study uses a quantitative research design, which is based on the positivist paradigm. This study was conducted first using in-depth interviews since conducting the initial survey and distributing questionnaires to respondents and then calculating three financial ratios to assess the quality of financial decisions. Furthermore, a quantitative analysis was carried out based on multivariate analysis using a structural equation model or SEM (structural equation modeling) based on Partial Least Square (PLS). The respondents selected in the study came from real sector MSMEs that received financing from the banking sector as many as 212 MSMEs. The results of the study showed that behavioral finance had a negative and significant effect on the company's financial decisions, which were stated as negative and significant. It can be concluded that the increase in Behavioral Finance as measured by Overconfidence, Representativeness, Herding, Anchoring, Cognitive Dissonance, Regret Aversion, Gambler's Fallace, Mental Accounting, Hindsight can reduce the quality of financial decisions as measured by the debt to asset ratio, capital structure ratio and retention ratio.